2009
DOI: 10.1021/la901285f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Nanoconfinement Induced Organization of n-Decane

Abstract: Molecular dynamics (MD) simulations are used to study the behavior of n-decane under sub-10 nm confinement between two gold {111} surfaces. This confinement and dielectric medium are characteristic of those used in nanoscale electromachining (nano-EM) processes; thus, it is important that the behavior of the nanoconfined dielectric medium be investigated for better process understanding. Results obtained via MD simulations indicate that, when confined down to a thickness less than 1 nm, the mechanical boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…2b, this densely packed state resembles a solid-like structure in the lubricant molecules because of the strong solid-fluid interaction. Kalyanasundaram et al [22] reported similar results. As the chain length increased the lubricant molecules tended to accumulate around the asperities and join the molecules from the opposite wall, as shown in Fig.…”
Section: Relaxation and Compressionmentioning
confidence: 63%
“…2b, this densely packed state resembles a solid-like structure in the lubricant molecules because of the strong solid-fluid interaction. Kalyanasundaram et al [22] reported similar results. As the chain length increased the lubricant molecules tended to accumulate around the asperities and join the molecules from the opposite wall, as shown in Fig.…”
Section: Relaxation and Compressionmentioning
confidence: 63%
“…Over the last two decades, there have been extensive studies of thin film lubrication of alkane between metal tribo-pairs using molecular dynamics (MD) method. [4][5][6][7] Attempts have been made to assess the role of Fe 2 O 3 (001) surfaces in thin film lubrication; [8][9][10] however, a thorough understanding of tribological and structural properties of hexadecane on different iron and iron oxides surfaces as well as their surface orientations is still missing. Additionally, previous investigations employed a simple model, in which each methyl or methylene group was described using a united-atom (UA) model and tribo-surfaces were modeled by harmonic spring without the consideration of electrostatic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-molecular interactions, including bond stretching, angle bending and dihedral angle torsion are governed by harmonic form, theta harmonic form and cosine polynomial form, respectively [25]. The corresponding equations and parameters are provided in Table 1.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Savio et al [24] investigated the friction properties of the last lubricant layers prior to direct contact of surfaces by considering several parameters. Kalyanasundaram et al [25] simulated the organizational behavior of n-decane for different gap separations (sub-10 nm) and found that the medium structures were affected by mechanical boundary conditions and crystallographic directions. Minimal investigations exist on anti-wear and anti-friction mechanisms of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%